Efeitos anti-inflamatório e antitumoral dos constituintes de Qualea grandiflora no tumor de Ehrlich - Quilles, Marcela Bassi [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Breast cancer is a leading cause of death among women, followed by cervix cancer. The treatments normally used are highly aggressive, and most often causing deleterious effects on host cells. Macrophages are the first cells to be activated to participate in an immune response itself, cells are able to secrete more than hundred biologically active products, among these, reactive nitrogen species and cytokines that act in the context of immune and / or inflammatory. Qualea grandiflora Mart (Q. grandiflora) family Vochysiaceae is a plant of the Brazilian Cerrado, used in folk medicine in the treatment of ulcers, gastritis, amebiasis, bloody diarrhea, intestinal cramps and inflammation. Previous studies in our laboratory have shown that species Qualea sp. showed in vitro antitumor activity extremely selective murine breast tumor (line LM3) and also has anti-inflammatory characteristics by the significant inhibition of the production of immune mediators NO, IL-1 and IL-12 by murine peritoneal macrophages activated with LPS. From these results, we propose to evaluate this work an alternative form of treatment for breast cancer by employing a crude extract (EH), a fraction terpene (FT) derived from the hexane extract of Q. grandiflora and substance isolated β-sitosterol (BS) in an experimental model of Ehrlich concomitant evaluation of the immunological effects of the tested substances in the animal. As standard drug of experiments, we used Taxol ® (Paclitaxel-TX). It has been determined in vitro cytotoxicity of peritoneal exudate cells of mice and Ehrlich tumor cells after incubation with the different treatments using the technique of MTT analysis of VEGF angiogenesis by measuring the ocorência apoptosis in tumor cells by techniques Tunel and annexin V as well as the inhibition of nitric oxide (NO) and TNF-α, IL-1, IL-12 and IL-6. In addition, it was determined the rate of in vivo tumor inhibition and histological analysis by light ...

O câncer de mama é uma das maiores causas de morte dentre as mulheres, seguido pelo câncer de colo de útero. Os tratamentos geralmente utilizados são extremamente agressivos e na maioria das vezes causando efeitos deletérios as células do hospedeiro. Os macrófagos são as primeiras células a serem ativadas para participar de uma resposta imunológica propriamente dita, são células capazes de secretar mais de cem produtos biologicamente ativos, entre esses, espécies reativas de nitrogênio e citocinas que atuam no contexto da resposta imunológica e/ou inflamatória. Qualea grandiflora Mart (Q. grandiflora) da família Vochysiaceae é uma planta do cerrado brasileiro, utilizada na medicina popular no tratamento de úlceras, gastrites, amebíase, diarréia com sangue, cólicas intestinais e inflamações. Estudos realizados anteriormente em nosso laboratório demonstraram que espécies de Qualea sp. apresentou atividade antitumoral in vitro extremamente seletiva para tumor de mama murino (linhagem LM3) e ainda apresenta características anti-inflamatórias através da inibição expressiva da produção dos mediadores imunológicos NO, IL-1 e IL-12 pelos macrófagos peritoneais murinos ativados com LPS. A partir destes resultados, propusemos avaliar neste trabalho uma forma alternativa de tratamento contra o câncer de mama experimental empregando-se um extrato bruto (EH), uma fração terpênica (FT) derivada do extrato hexânico de Q. grandiflora e a substância isolada β-sitosterol (BS), em modelo experimental de Ehrlich concomitante à avaliação dos efeitos imunológicos das substâncias testadas, no animal. Como droga padrão dos experimentos realizados, utilizou-se o Taxol® (Paclitaxel- TX). Foi determinado in vitro a citotoxicidade celular de células do exsudado peritoneal de camundongos e células tumorais de Ehrlich, após incubação com os diferentes tratamentos pela técnica de MTT, analise da angiogênese pela dosagem...
Keywords: Mamas - Cancer - Prevenção; Apoptose; Neovascularização; Vochysiaceae; Imunologia clínica; Plantas - Compostos bioativos; Apoptosis